2015
DOI: 10.1097/prs.0b013e31829b69fe
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cost Analysis of Cleft Lip Adhesion and Nasoalveolar Molding before Formal Cleft Lip Repair

Abstract: Nasoalveolar molding may cost less before formal cleft lip repair treatment than cleft lip adhesion. Third-party payers who cover adhesion and not nasoalveolar molding may not be acting in their own best interest. Nasoalveolar molding places a higher burden of care on families, and this fact should be considered in planning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 17 publications
0
46
0
1
Order By: Relevance
“…In addition to the clinical benefits and risks of labial adhesion, expenditure on health care became a subject of growing focus. A recent published study performed a retrospective comparative cost analysis of labial adhesion and nasoalveolar molding (Shay et al , ). This study demonstrated that nasoalveolar molding had distinct financial advantages over labial adhesion, but also placed a higher burden of care on families.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clinical benefits and risks of labial adhesion, expenditure on health care became a subject of growing focus. A recent published study performed a retrospective comparative cost analysis of labial adhesion and nasoalveolar molding (Shay et al , ). This study demonstrated that nasoalveolar molding had distinct financial advantages over labial adhesion, but also placed a higher burden of care on families.…”
Section: Discussionmentioning
confidence: 99%
“…Among included studies, Shen et al [ 53 ] and Chen et al [ 54 ] evaluated the cost of cleft treatment and demonstrated that the NAM appliance has the potential to decrease the overall cost of cleft treatment. Two excluded retrospective studies confirmed this trend [ 30 , 31 ], NAM appeared indeed as a great mean to reduce the complexity, the number of the repair surgeries and subsequently the cost of care. One of them published by Shay et al in 2015 [ 31 ], gives interesting results and showed that the cost of a group of patients treated with NAM (mean costs $ 3550.24 ± $ 667.27) is significantly lower compare to a group of patients who received a surgical clef lip adhesion without NAM (mean costs $ 9370.55 ± $ 1691.79).…”
Section: Discussionmentioning
confidence: 90%
“…Two excluded retrospective studies confirmed this trend [ 30 , 31 ], NAM appeared indeed as a great mean to reduce the complexity, the number of the repair surgeries and subsequently the cost of care. One of them published by Shay et al in 2015 [ 31 ], gives interesting results and showed that the cost of a group of patients treated with NAM (mean costs $ 3550.24 ± $ 667.27) is significantly lower compare to a group of patients who received a surgical clef lip adhesion without NAM (mean costs $ 9370.55 ± $ 1691.79). No study related to parent’s cooperation during NAM therapy was included.…”
Section: Discussionmentioning
confidence: 90%
“…The so called "digital revolution" that affected dentistry over the last ten years now involves almost all the different dental specialties, making a growing number of manual tasks easier and faster to perform, cheaper, and more predictable [16]. It started with dental technicians' labs following the development of different systems of subtractive machining technology, which are now progressively integrated and sometimes substituted by additive processes for layered fabrication, and then included dental therapists, thanks to the diffusion of IOS and CAD-CAM systems designed to realize a chair-side restorative management of all individualized dental devices [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because of neonatal cartilage plasticity, due to high levels of circulating hyaluronic acid, that allow the correction of the nasal cartilage and soft tissue deformity [14]. Pre-surgical nasoalveolar molding results in long-term benefits to the patient and medical economics [15,16].…”
Section: Introductionmentioning
confidence: 99%